2012
DOI: 10.1371/journal.pone.0040376
|View full text |Cite|
|
Sign up to set email alerts
|

The PNPLA3 rs738409 G-Allele Associates with Reduced Fasting Serum Triglyceride and Serum Cholesterol in Danes with Impaired Glucose Regulation

Abstract: Background and Aim Non-alcoholic fatty liver disease (NAFLD) is a common condition, associated with hepatic insulin resistance and the metabolic syndrome including hyperglycaemia and dyslipidemia. We aimed at studying the potential impact of the NAFLD-associated PNPLA3 rs738409 G-allele on NAFLD-related metabolic traits in hyperglycaemic individuals. Methods The rs738409 variant was genotyped in the population-based Inter99 cohort examined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
(44 reference statements)
6
17
0
Order By: Relevance
“…The rs738409 variant similarly confers risk for increased histological severity dissociated from its effects on central obesity and IR [157,158] . Its pathogenic role in impaired lipid homeostasis as evidenced by a peripheral decrease in serum triglyceride, total and high-density lipoprotein cholesterol [159,160] is furthermore unmasked in the presence of increased visceral adiposity [161] and impaired glucose tolerance [162] , in addition to being modulated by lifestyle and dietary habits [161,163] . It has further been proposed that lipotoxicity and inflammatory stress resulting from impaired intra-hepatic lipid metabolism and free cholesterol deposition associated with PNPLA3 rs738409 activates dormant hepatic stellate cells (HSCs), leading to increased fibrogenesis.…”
Section: Incorporation Of Personalized Genomic Testing To Existing Comentioning
confidence: 99%
“…The rs738409 variant similarly confers risk for increased histological severity dissociated from its effects on central obesity and IR [157,158] . Its pathogenic role in impaired lipid homeostasis as evidenced by a peripheral decrease in serum triglyceride, total and high-density lipoprotein cholesterol [159,160] is furthermore unmasked in the presence of increased visceral adiposity [161] and impaired glucose tolerance [162] , in addition to being modulated by lifestyle and dietary habits [161,163] . It has further been proposed that lipotoxicity and inflammatory stress resulting from impaired intra-hepatic lipid metabolism and free cholesterol deposition associated with PNPLA3 rs738409 activates dormant hepatic stellate cells (HSCs), leading to increased fibrogenesis.…”
Section: Incorporation Of Personalized Genomic Testing To Existing Comentioning
confidence: 99%
“…The I148M variant influences liver fat without independently of body mass index, dyslipidemia, or insulin resistance, and it has been associated with severe steatosis, NASH, and liver fibrosis (Valenti et al 2002(Valenti et al , 2006(Valenti et al , 2010aMiele et al 2008;Dongiovanni et al 2010), even if severe obesity exposed an association between I148M, insulin resistance, and lower triglycerides in Northern European subjects (Krarup et al 2012;Palmer et al 2012). We previously showed that in overweight children with increased liver enzymes, the PNPLA3 I148M polymorphism is enriched compared to the general population (homozygosity for the 148M risk allele was 16 vs. 5 % in the general population) and represents a non-invasive early marker of NASH and fibrosis (Valenti et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…PNPLA-3 G alleles appear strongly associated with steatosis, steatohepatitis and fibrosis progression in alcoholic and nonalcoholic fatty liver disease (15,17) as well as hepatitis C related liver disease (16,23). In this study the G allele frequency appears slightly higher in the liver transplant recipient population (29%) than in the general population ($21% to 25%) (14,18,19,24). However, the frequency of GG polymorphism is close to twice the normal population (which is $5%) (19,25), possibly relating to the increased risk of liver disease progression, resulting in a GG enriched population.…”
Section: Discussionmentioning
confidence: 40%
“…However, the frequency of GG polymorphism is close to twice the normal population (which is $5%) (19,25), possibly relating to the increased risk of liver disease progression, resulting in a GG enriched population. Although some studies have suggested less of an association of PNPLA-3 polymorphisms with insulin resistance or obesity (14,18,19,26), mechanistic studies have linked glucose metabolism and obesity with PNPLA-3 stimulation and protein production in the insulin sensitive individual (24,27,28). This study extends the link between PNPLA-3 gene polymorphisms and obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation